Catastrophes, public calamities or major disasters: legal instruments for the management of local emergencies and the role of the mayor - Ricard Brotat i Jubert (Revista d'Estudis Autonòmics i Federals, 2025)
In the event of a ‘catastrophe, public calamity or serious risk thereof’, the mayor has the power to personally adopt, and therefore be responsible for, the necessary and adequate measures. This work reviews the normative antecedents of this power, the areas in which it is usually exercised, the impact on the fundamental rights and the principle of health protection, and the jurisprudence established in this matter.